2015
DOI: 10.1002/chem.201500060
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Asymmetric Three‐Component Borylstannation: Enantioselective Formation of CSn Bond

Abstract: In summary, a first copper-catalyzed synthesis of a-aryl-b-borylstannane compounds was accomplished through three-component borylstannation of aryl-substituted alkenes. In the exploration of an asymmetric variant, chiral sulfinylphosphine ligands proved advantageous in controlling stereochemistry of BÀCu addition and in promoting transmetalation of enantioenriched alkylÀCu species. The stereochemical outcome supported a sequential syn-borylcupration and configuration-retentive transmetalation mechanism. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 95 publications
1
26
0
Order By: Relevance
“…The asymmetric borylstannation of alkenes was also accomplished by using a copper/chiral sulfinylphosphine catalyst . This reaction used B 2 (pin) 2 as a borating reagent and R 3 SnOMe as a tin source and led to the production of various α‐aryl‐β‐borylstannane compounds in good‐to‐high yields with high ee .…”
Section: Copper Catalysismentioning
confidence: 99%
“…The asymmetric borylstannation of alkenes was also accomplished by using a copper/chiral sulfinylphosphine catalyst . This reaction used B 2 (pin) 2 as a borating reagent and R 3 SnOMe as a tin source and led to the production of various α‐aryl‐β‐borylstannane compounds in good‐to‐high yields with high ee .…”
Section: Copper Catalysismentioning
confidence: 99%
“…R 1 = 1-Na p h, R 2 = Ph: 94%, 96% de, 94% ee R 1 = o-Tol , R 2 = Ph: 83%, 84% de, 94% ee R 1 = p -MeOC 6 H 4, R 2 = Ph: 70%, 80% de, 88% ee R 1 = p -FC 6 H 4, R 2 = Ph: 87%, 84% de, 88% ee R 1 = ( E ) -PhCH=CH , R 2 = Ph: 66%, 92% de, 92% ee R 1 = ( E ) -PhCH=C ( Me ), R 2 = Ph: 86%, 88% de, 86% ee R 1 = CH 2 Bn, R 2 = Ph: 80%, 96% de, 85% ee R 1 = Ph, R 2 = p -MeOC 6 H 4 : 69%, 90% de, 96% ee R 1 = Ph, R 2 = p -F 3 CC 6 H 4 : 79%, 80% de, 84% ee R 1 = Ph, R 2 = 2-thien y l: 73%, 94% de, 92% ee R 1 = Ph, R 2 = SiEt 3 : 83%, 88% de, 70% ee In 2015, asymmetric copper-catalyzed borylstannations of aromatic alkenes 136, B 2 (Pin) 2 and Bu 3 SnOMe were developed by Liao et al, as shown in Scheme 48 [59]. Using a chiral catalyst in situ generated from CuCl and chiral sulfinylphosphine ligand 137, the three-component reaction afforded the corresponding chiral α-arylβ-borylstannanes 138 in moderate to quantitative yields (63-99%) and good to high enantioselectivities (86-96% ee).…”
Section: ( 5 Mol% )mentioning
confidence: 99%
“…Other functionalizations of alkenes, such as asymmetric borylstannations, have been very recently described by Liao et al 126. This study dealt with an enantioselective copper‐catalyzed three‐component reaction between styrenes 295a–n , B 2 (pin) 2 and Bu 3 SnOMe performed at 20 °C in the presence of chiral sulfinylphosphine ligand 296 and CuCl as precatalyst in THF as solvent (Scheme ).…”
Section: Enantioselective Metal‐catalyzed Multi‐component Reactionsmentioning
confidence: 99%